Lactic acid contributes to the emergence of depression-like behaviors triggered by blue light exposure during sleep - Yinhan Li; Xinhui Zou; Ying Ma; Jiaqi Cheng; Xiangmin Yu; Wenya Shao; Fuli Zheng; Zhenkun Guo; Guangxia Yu; Siying Wu; Huangyuan Li; Hong Hu (Ecotoxicology and Environmental Safety)
The threat posed by light pollution to human health is increasing remarkably. As demand for high-efficiency and bright lighting increases, so does the blue light content from artificial sources. Although animal studies suggested blue light induced depression-like behaviors, human evidence remained limited, and the mechanisms by which blue light affects depression remained elusive. This study aimed to investigate the association between blue light exposure and depression in humans, and explored the underlying mechanisms that driving depression-like behaviors induced by blue light. Our population findings showed that the high-blue-light exposure at night was positively associated with depressive symptoms. Lactic acid was relevant to depression with Mendelian randomization analysis. Moreover, animal studies demonstrated that exposure to blue light during sleep (BLS) induced depression-like behaviors in the animals. Metabolomics and colorimetric analyses revealed elevated levels of lactic acid in the cerebrospinal fluid and lateral habenula (LHb) of rats with depression-like behaviors induced by BLS. The administration of a lactate inhibitor (Oxamate) alleviated these behaviors, along with changes in neuronal excitability, synaptic function, and morphology in the LHb. Overall, our study suggests that excessive exposure to high blue light-content artificial light at night links to increased depressive symptoms, revealing possible molecular mechanisms and prevention strategies, which are crucial for addressing environmentally related mental health issues.